Examining the relationship among TQM, organizational learning and innovation performance - Yusr, Maha Mohammed; Mohd Mokhtar, Sany Sanuri; Othman, Abdul Rahim (International Digital Organization for Scientific Information (IDOSI), 2013)
TQM and organizational learning are considered as management practices that can enhance innovation performance.However, the question still remains regarding the nature of relationship among these concepts.Although there are many studies in the literature, most of them are prescriptive and case studies which did not provide evidence that can be generalized.Thus, this study examines the relationships among TQM practices, organizational learning capability and innovation performance and determines the mediating relationship between TQM and innovation performance through organizational learning.The data were collected by using on-line survey approach to manufacturing companies.One hundred and thirty nine Malaysian manufacturing companies participated in this study.The findings of this study supported all hypotheses.